The Silencing of Student Movement Against The Egyptian Pro-Capitalism Government in Radwa Ashour's Novel Faraj - Shinta Fitria Utami; Betty Mauli Rosa Bustam (Center of Middle Eastern Studies (CMES), 2021)
This research is studying about novel Faraj. The novel contains an overview of the silencing the student movement’s resistance during the capitalist government. This resistance rises due to the cooperation policy between Egypt and the U.S, which impact on intervention of the U.S in Egypt economic and political affairs. The Egyptian students begin, intensively, to discuss these issues, write numerous articles about resistance and criticism of the government, and perform various protests in Cairo. The method of data collecting data in this research consist of two phases, determines the research object and restriction on research problems that focused on an overview of events related to silencing the student movement. The method of data processing consists of determining the relevant theory to answer the problem, searching for references that support the research topic, analyzing the data in accordance with the related theory. The Result of this research indicates the silencing carried out against the anti-capitalist student movement in Egypt. The silencing was conducted through the destruction of the wall magazine, which publish numerous articles about resistance and criticism of the government, arrest, and torture. It happened because of the different interests between the government and the students.